1976
DOI: 10.1002/1097-0142(197611)38:5<2111::aid-cncr2820380539>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Calcium metabolism in cancer.Studies using calcium isotopes and immunoassays for parathyroid hormone and calcitonin

Abstract: Studies of calcium metabolism in 38 patients with cancer indicated that: 1) intestinal absorption of calcium was reduced in patients with skeletal metastases and in those with hypercalcemia; 2) calcium-47 space (a measurement of bone turnover rate) was high in the patients with skeletal metastases; 3) hypercalcemic patients had higher urinary and endogenous fecal excretion of calcium than those who were normocalcemic; 4) levels of plasma immunoreactive parathyroid hormone were similar in normo-and hypercalcemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 25 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…22 Other sources of calcium appear to be less important as demonstrated by isotope studies which typically show a decrease in intestinal absorption of calcium in these patients. 23 The decrease is presumably mediated by the low levels of 1,25-dihydroxy-vitamin D usually observed.24 Renal tubular calcium reabsorption also is usually decreased in most patients with paraneoplastic hypercal~emia.~~?~~…”
Section: Discussionmentioning
confidence: 99%
“…22 Other sources of calcium appear to be less important as demonstrated by isotope studies which typically show a decrease in intestinal absorption of calcium in these patients. 23 The decrease is presumably mediated by the low levels of 1,25-dihydroxy-vitamin D usually observed.24 Renal tubular calcium reabsorption also is usually decreased in most patients with paraneoplastic hypercal~emia.~~?~~…”
Section: Discussionmentioning
confidence: 99%
“…In fact, malignant disease is thc most common cause of hypercalcacmia in hospitaliscd patients [177]. The cause is uncertain.…”
Section: Fluid and Electrolyte Disturbancesmentioning
confidence: 99%
“…The cause is uncertain. It has been suggested that, in patients with bone metastases, hypercalcaemia is due to the release of calcium following bone destruction [177]. It is clear, however, that hypcrcalcaemia can arise even when there is no direct bonc involvement when removal of the tumour may result in the return of serum calcium to within the normal rangc.…”
Section: Fluid and Electrolyte Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accelerated net bone resorption is believed to be the source of the hypercalcemia in such patients (1,4,5), although understanding of the mechanisms whereby malignant cells alter the functions of normal bone cells remains incomplete. Direct osteolysis by tumor cells metastatic to bone may occur (6).…”
Section: Introductionmentioning
confidence: 99%